Intelligent thermoregulation and homeostasis: lessons from nature - Worall, Mark (2010)
Mankind has developed sophisticated means of maintaining comfortable living conditions around the world. We use many technologies that allow us to achieve thermoregulation and homeostasis and so live, work and survive in otherwise hostile environments. Many species in nature also practice thermoregulation and homeostasis, with some of the most interesting being the social insects. Biomimetics is defined as design inspired by nature, and so a biomimetic approach to thermoregulation might enable engineers to develop novel strategies that have less of an impact on natural resources and are more responsive to the environment. The mound building termites of South America, Africa and Australasia construct sophisticated structures that enable the environment within the nest to be regulated. Wind energy is captured to exchange gases between the nest, the mound and the outside by elaborate internal galleries, tunnels, and ducts. Gas exchange and ventilation could be achieved through responsive envelopes and fabric analogous to termite homeostasis. The oriental hornet can maintain a nest temperature of 28-32°C in tropical, sub-tropical and temperate areas. It has been found that when the adult population are removed from the nest, its temperature is maintained for a number of days afterwards. The oriental hornet nest houses both the adult population and combs that contain the brood. Eggs are placed in the walls of the comb and when they hatch the pupa spin a silk weave and form a silk cap at the open entrance, sealing it from the outside. In studying the thermoregulatory properties of hornet nests, it has been shown that the silk cap and walls of the comb have thermoelectric properties that could help regulate the temperature in the comb. It was shown that as ambient temperature increases, the current intensity increases. When the ambient temperature falls the energy stored is discharged with a flow of electric current from high to low potential. The engineering materials with properties closest to the Hornet silk are the conductive polymers, although the thermoelectric properties may be more than 10,000 times lower than semiconductors used in modern devices they may be useful as heat storage and discharge systems in buildings.